A Detailed Decomposition of Changes in Wage Inequality in Reunified Post-transition Germany 1999-2006: Accounting for Sample Selection - Usamah Fayez Al-Farhan (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In this article, I analyze the changes in wage inequality in the eastern region, western region and reunified Germany a decade after reunification. For that purpose, I use data from the German Socio-Economic Panel for the period 1999 - 2006, and implement the decomposition methodologies of Fields (2003) and Yun (2006). I find that during the sub-period 1999-2002 each of the characteristics effect, coefficient effect and residual effect contributed to the increasing levels of wage inequality in Germany. On the other hand, the relative stability in wage inequality during the sub-period 2002-2006 was caused by the fact that the characteristics effect and the residual effect influenced wage inequality negatively, whereasthe coefficient effect maintained a positive influence in both the western region, eastern region and in reunified Germany alike. Hence, I conclude that after 1999, changes in wage inequality in Germany can be explained by both; changes in workers characteristics and changes in the wage structure, and not by changes in the wage structure alone, as the case has been during the transition process in the first decade after reunification
Keywords: D30; J31; 330; Wages; Inequality; Decomposition; Transition; Characteristics effect; Coefficient effect; Residual effect; Selection bias; Maximum Likelihood; Lohnstruktur; Regionale Lohnstruktur; Soziale Ungleichheit; Deutschland; Wirtschaftliche Anpassung; Ostdeutschland